Obraz I wojny światowej w tzw. "Pamiętniku Galicjanki (1914-1917)" = Image of the First World War in the so-called "Pamiętnik Galicjanki" (Galician`s Diary) "(1914-1917)" - Jazownik, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the literary and documentary values of memoirs of Maria of the Bochdans Obertyńska (1861-1956) published in 2012 under the title "Pamiętnik Galicjanki" (Galicjan`s Diary) "(1914-1917)" and incorrectly attributed to Magdalena Bylczyńska (1887-1966).
Keywords: Polish diary keeping; "Kurier Lwowski"; First World War; Eastern Galicia; civilians; collective consciousness; landed gentry ethos; pamiętnikarstwo polskie; I wojna światowa (1914-1918); Galicja; świadomość zbiorowa; ziemiaństwo